Reducing Non Performing Financing Through Financial Ratios - Maya Indriastuti; Indri Kartika; Sri Sulistyowati (Faculty of Economics and Business | Universitas Diponegoro, 2020)
The aim of this study is to investigate financial ratios in minimizing non performing financing (NPF) at Sharia Banks. The samples of this study were 11 Sharia Banks listed in Bank Indonesia in 2008-2018. The data were analyzed by using multiple linier regression analysis. The result of this study showed that CAR, QPA, and OEOI have a significant positive effect on NPF. Meanwhile, FDR variable has no significant negative effect on NPF. The results of this study are expected to provide information on the factors that can affect the NPF and how to control the NPF so that Sharia Banks can keep the ratio of NPF net to stay under 5%, this is to maintain the condition of the bank soundness level.